Leadership Character Development Strategy Through Islamic Fair Activities at SMP Muhammadiyah 7 PU Colomadu (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This research aims to describe the strategy for leadership character development implemented at SMP Muhammadiyah 7 PU Colomadu through the Islamic Fair activities, and to identify the supporting and inhibiting factors in its implementation. The research employs a qualitative approach with a phenomenological method and a case study design. Data collection was conducted through observation, semi structured interview with the school principal, supervising teachers, and students, as well as documentation. Data analysis uses the interactive model of Miles and Huberman, which includes data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that leadership character development is carried out systematically through the integration of the school’s vision and mission, student committee structure, intensive teacher mentoring, and continuous evaluation based on the POAC management principles (Planning, Organizing, Actuating, and Controlling). The Islamic Fair activities serve as an effective experience-based learning medium in fostering leadership values such as responsibility, cooperation, communication, and self-confidence among students. The main inhibiting factors stem from the student’s psychological aspects, especially the lack of self-confidence and mental readiness in accepting responsibility. This research provides theoretical and practical contributions to the development of a leadership character development model at the junior high school level.